PENINGKATAN MOTIVASI BELAJAR SISWA SECARA ONLINE PADA PELAJARAN ANIMASI 2D MELALUI STRATEGI KOMUNIKASI PERSUASIF - Arifah Suryaningsih (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2020)
This best practice reports online learning activities during the Covid-19 pandemic period. This study was conducted to determine the influence of persuasive communication strategy to the relationship between learning motivation and students' creative enthusiasm in making 2D animations. Subject of the study was 64 students in class of XI Multimedia at SMK Negeri 2 Sewon, Bantul. The results of this study indicate that student motivation decreased at the 5th week of school from home (SFH) program. The application of persuasive communication strategy for students that was carried out in this study both in groups and privately increase their motivation and creativity during the completion of their assigments. There was also an increase of response in the WhatsApp group for direct submission of student assignments as well as accomplishment of assignments that had to be uploaded in the student's personal social media.